The investigation of the shelf life at 2 ± 1 A°C of Luciobarbus esocinus fillets packaged with films prepared with the addition of different essential oils and chitosan - Kuzgun, Nermin Karaton; Inanli, Ayse Gurel (Springer India, 2018)
In this study, the chemical, microbiological and sensory changes during storage at 2 +/- 1 A degrees C of Luciobarbus esocinus fillets coated with edible films prepared with chitosan incorporation of thyme, clove, rosemary essential oils were examined. To create the experimental samples, a total of six groups of L. esocinus fillets coated with different edible films (normal, vacuum-packed, chitosan, chitosan with added thyme oil, chitosan with added clove oil, and chitosan with added rosemary) were used. The food composition of the fillets and experimental samples were determined after they had been coated with edible films. The results of analysis showed that, the preservation period of fresh fillets ended on day 12th, that of vacuum-packed fillets on day 15th, that of fillets coated with chitosan incorporation of rosemary on day 27th, that of fillets coated with chitosan incorporation of thyme and chitosan incorporation of cloves on day 30th. In comparison with the control group, fish spoilage was significantly delayed in samples coated with chitosan incorporation of thyme and chitosan incorporation of cloves (p < 0.05). The lowest bacterial growth, values of PV, TBA and TVB-N were obtained in fish samples coated with thyme + chitosan and cloves + chitosan. In terms of the general acceptability of the fish, as determined by qualified panelists, it was determined that the highest score was given to the experimental group to which essential oil of clove had been applied.
Keywords: Chitosan; Edible film; Luciobarbus esocinus; Essential oil; Shelf-life